PENGARUH KEPUASAN PELANGGAN MAHASISWA UNSIKA TERHADAP KUALITAS KETEPATAN WAKTU KERETA API LOKAL KARAWANG-CIKARANG - Haryanto, Khensa Aqilla; Sudrajat, Ajat (Growth, 2024)
The aim of this study was to find the effect of punctuality of local train services on the Karawang-Cikarang route on customer satisfaction of Singaperbangsa University of Karawang (UNSIKA) students. Punctuality is a crucial aspect in the passenger's travel experience in rail transportation services. The study method applied was descriptive quantitative, with 177 respondents of UNSIKA students who use local train services on the route through questionnaire distribution. Using a simple linear regression test, the data were analyzed. The study findings show that punctuality positively and significantly affects customer satisfaction. It is proven that about 33.5% of customer satisfaction can be explained by punctuality. This study highlights that the punctuality of Karawang-Cikarang local trains plays an important role in improving customer satisfaction, and suggests that train service operators increase attention and performance in terms of punctuality.